PENGEMBANGAN MEDIA ONLINE SEBAGAI SARANA KOMUNIKASI DAN PROMOSI YAYASAN PUTRA FITRI - Agus Hitopa Sukma; Erita Riski Putri; Iswahyu Pranawukir; Sylvia Kartika Dhamayanti; Nur Desilawati (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
The use of new media in communication shows a form of interaction that has added value. By training in communication skills through online media, creative and innovative ideas will develop, especially for promotions. This is the target of service activities for teachers at the Putra Fitri Foundation/An-Nabil Bojonggede PAUD school. Therefore, the aim of the activity is to provide digital literacy skills in using online media and the ability to write using computer media or smart devices to the teachers of the Putra Fitri Foundation/An-Nabil Bojonggede PAUD school so that they can increase their creative and innovative abilities in carrying out promotions. The form of activity is counseling and training. The results of the activity show that the development of online media in the form of websites, social media and mobile applications has had a positive impact in increasing interaction between schools and parents, the community and related stakeholders as well as increasing community interest in registering their children at An-Nabil Bojonggede PAUD School. The implication of this research is the importance of using online media as a means of communication and promotion in improving the quality of early childhood education services.